(untitled) (Journal of Economic Research & Business Administration, 2015)
Typically, the reason for development and implementation of innovative products is a customer of the bank. This article discusses necessity to introduce innovations in the banking business and its historical process. Main types of innovation arose due to the needs of the client. Bank makes concessions to the client as a legal or natural person, who contacts with the bank to make credit, deposit, settlement, foreign currency and other transactions, thereby introducing a new service, a new initiative, or any other new products. Many scientists expressed their opinion regarding the occurrence of innovation in the banking business. Most of them, came to the conclusion that innovation is the driving force behind the development of humanity, which also contributes to the growth of the economy. At the moment, many foreign banks are specialized to create the units of innovation. Also, the article discusses the first computer ERMA, the device which has several innovative solutions, and other products , which were originally introduced Bank of America.